0256 Circadian Rhythms, Impulsivity, and Adolescence: Effects Of Circadian Misalignment on the Neural Response During the Go/No-go Task In Human Adolescents. (27th April 2018) - Logan, R W; Shafer, A R; Ngari, W; Hasler, B P
Abstract: Introduction: During adolescence, sleep timing and circadian rhythms gradually delay, with a shift towards an evening preference. This delayed sleep/circadian timing conflicts with early school start times, resulting in a mismatch between sleep-wake schedules and internal circadian timing, or circadian misalignment. This circadian misalignment is linked to poor executive function, impaired impulse control, and altered neural responses to reward, all of which may contribute to substance use vulnerability. In the present study, we investigated the effect of circadian misalignment on the neural correlates of response inhibition in healthy adolescents. Methods: Healthy adolescents (n=22, ages 13–17) performed the Go/No-Go task (block design with Go inputs, No-Go inputs, or Rest) and underwent task-related fMRI scans. Participants were subjected to aligned conditions based on typical summer sleep-wake times (midnight-9:30am) and misaligned conditions set to four hours earlier (8pm-5:30am). Within-subject comparisons between misaligned and aligned conditions focused on No-Go&gtRest contrasts to capture correlates of active response inhibition. Dim Light Melatonin Onset (DLMO) was used as an endogenous circadian phase marker to account for individual differences. Results: Adolescents responded with similar accuracies and response times between aligned and misaligned conditions, suggesting minimal impact of circadian condition on task performance. The within-subject comparison between the aligned and misaligned conditions (aligned&gtmisaligned) revealed significantly reduced activation of brain regions previously known to be involved in response inhibition, including the caudate, putamen, insula, and inferior frontal gyrus (IFG). No regions showed greater activation during the misaligned condition. Overall patterns of neural activation remained consistent even after accounting for DLMO, suggesting individual differences of circadian phase did not account for differences between conditions. Conclusion: Circadian misalignment had a significant impact on neural correlates of response inhibition, including reduced activation in several regions (e.g., IFG) previously associated with substance use in adolescents and implementation of inhibitory control. Furthermore, reduced activation was observed in areas (e.g., caudate) associated with motivation, suggesting misalignment potentially affects reward and cognition. Support (If Any): K01DA038654 (Logan) and K01DA032557 (Hasler).